Meningkatkan Kemandirian Belajar Mahasiswa Pendidikan Matematika di Masa Pandemi Covid-19 melalui Pembelajaran Blended Learning - Rasid Ode; Kasriana Kasriana; Safarin Zurimi (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2021)
This research was conducted at Darussalam University Ambon with the research subjects being students of mathematics education in the third semester of the academic year 2021/2022. This study aims to determine student responses to learning independence through blended learning using several indicators of learning independence. The results showed that most (80%) students in the third semester of the Mathematics Education Study Program at the University of Darussalam Ambon were in the good category with the following description: : (1) 69% of students have learning initiatives; (2) diagnose the learning needs of 76% of students; (3) setting the target or learning objectives owned by students as much as 73%; (4) monitor, regulate and control 81% owned by students; (5) views difficulties as challenges that are owned by 73% of students; (6) utilize and look for relevant sources owned by students as much as 75%; (7) choose and apply learning strategies owned by students as much as 77%; (8) evaluate the process and learning outcomes owned by students as much as 75%; (9) students' self-efficacy (self-concept) is 78%.